2022
DOI: 10.3390/pharmaceutics14051020
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent Plasma Therapy, Therapeutic Formulations of Repurposed Drugs in 20th Century Epidemics against COVID-19: A Systematic Review

Abstract: Coronavirus 2019 disease (COVID-19) represents one of the largest pandemics the world has faced, and it is producing a global health crisis. To date, the availability of drugs to treat COVID-19 infections remains limited to supportive care although therapeutic options are being explored. Some of them are old strategies for treating infectious diseases. convalescent plasma (CP) therapy has been used successfully in other viral outbreaks in the 20th century. In this study, we systematically evaluated the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Intravenous infusion of convalescent plasma therapy has been proposed as an alternative for immunization of these patients. Convalescent plasma therapy was used successfully in other viral outbreaks in the 20th century [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous infusion of convalescent plasma therapy has been proposed as an alternative for immunization of these patients. Convalescent plasma therapy was used successfully in other viral outbreaks in the 20th century [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Наличие антител к инфекционному агенту в трансфузионной среде, с одной стороны, со-пряжено с повышением вероятности развития у реципиента аллоиммунизации, особенно в случае множественных трансфузий, а с другой стороны, вероятно, способно оказать терапевтический эффект не только с точки зрения улучшения плазменного звена гемостаза, но и с точки зрения профилактики инфекции. Плазму реконвалесцентов применяли для пассивной иммунизации с начала ХХ века при борьбе с патогенами как вирусной, так и бактериальной природы [11,12]. Существуют описания применения гипериммунной плазмы в пандемию вируса гриппа (испанки) в 1918-1919 гг., затем в 1960-х годах -при борьбе с вирусом аргентинской геморрагической лихорадки, в 2003 г.…”
Section: Discussionunclassified
“…CD4 + T cells then drive B cells to make virus-specific antibodies, while cytotoxic CD8 + T cells attack virus-infected cells [ 48 ]. In addition, it was reported that more than 70% of COVID-19 convalescent patients had SARS-CoV-2-specific T cells [ 49 ].…”
Section: Discussionmentioning
confidence: 99%